2020
DOI: 10.47176/mjiri.34.55
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress due to COVID-19 in Iran: Emphasizing the role of social networks

Abstract: Rising mortality rate due to Corona virus (COVID-19) has raised anxiety and panic among the Iranian community. This reaction to COVID-19 may cause harm to people and even lead to some implications which raise more concerns than the Coronavirus itself. Previous research has shown that receiving this stimulating news has the same effect as posttraumatic stress and depression. →What this article adds:This study showed that perceived stress due to COVID-19 in Iranian society was slightly high and receiving news an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…Many studies have already been conducted about the effects of trust in social media on people’s anxiety and stress levels. In nearly every case, anxiety and stress levels were associated with greater media consumption, and often with perceived trust [ 14 , 15 , 61 , 62 ]. The overloading of informational reading on social platforms (i.e., Facebook, Instagram, Twitter) can make people anxious during quarantine and isolation due to concerns about their family or friends being affected by the virus [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have already been conducted about the effects of trust in social media on people’s anxiety and stress levels. In nearly every case, anxiety and stress levels were associated with greater media consumption, and often with perceived trust [ 14 , 15 , 61 , 62 ]. The overloading of informational reading on social platforms (i.e., Facebook, Instagram, Twitter) can make people anxious during quarantine and isolation due to concerns about their family or friends being affected by the virus [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to determine how the appropriate events and happenings affect the social discourse, discover and understand socio-cultural realities based on analyzing the prevailing attitude of the Iranian society towards the Corona issue, and their attention to scientific, religious, health and medical subjects. Previous studies have confirmed the large effect of social media on social awareness, mental health, and behavior after the outbreak [5] , [7] , [16] , [44] . One study found out that despite the stay-at-home orders issued by the organizations, the role of friends and families should be emphasized to promote compliance to the protocols [45] .…”
Section: Summary and General Analysismentioning
confidence: 70%
“…Contrary to that, in the last two months such words are among the most probable words of the corpus and cover over 40 and 60 percent, respectively. Though the gradual rise of miscellaneous topics may decrease the level of public stress caused by the social media contents [44] , as the social media mostly present personal opinions, the real condition of the disease may be neglected because of misinformation [16] caused by this considerable decrease in coronavirus-related topics. This may encourage people to escape to the safety of collective ignorance which reduces the compliance to protocols.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of a study ( 88 ) showed that higher COVID-19 perceived stress was associated with more emotional distress including fear and anxiety. It has been indicated that perceived stress due to COVID-19 among the Iranian general population was slightly high, and it has been correlated with using social media ( 89 ). Previous studies have also shown that, in some cases, social media can increase the perceived risk of the outbreaks ( 90 ).…”
Section: Discussionmentioning
confidence: 99%